2020
DOI: 10.1002/cld.843
|View full text |Cite
|
Sign up to set email alerts
|

60 Days in Biliary Atresia: A Historical Dogma Challenged

Abstract: http://aasldpubs.onlinelibrary.wiley.com/hub/journal/10.1002/(ISSN)2046-2484/video/15-s1-reading-tessier a video presentation of this article

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…In our case, ultrasonography, hepatobiliary scintigraphy, and liver biopsy confirmed the diagnosis of biliary atresia. Early diagnosis, ideally earlier than 30–45 days, followed by the Kasai procedure, results in better outcomes 12 . In our case, the Kasai operation was performed on the 40th day of life.…”
Section: Discussionmentioning
confidence: 70%
“…In our case, ultrasonography, hepatobiliary scintigraphy, and liver biopsy confirmed the diagnosis of biliary atresia. Early diagnosis, ideally earlier than 30–45 days, followed by the Kasai procedure, results in better outcomes 12 . In our case, the Kasai operation was performed on the 40th day of life.…”
Section: Discussionmentioning
confidence: 70%
“…Patients from the most recent cohort in that study (2010 to 2015) had 87% 5-year survival, an improvement from 72% in the first part of the study (1986 to 1996). This trend is naturally expected with accumulated experience over the years, and the awareness that the 60-day paradigm for KPE must be shifted to early intervention in the course of the disease ( 23 ).…”
Section: Discussionmentioning
confidence: 89%
“…In our group of patients, except for a patient operated at 196 days of age, the mean age at surgery was 58 days (42–84 days), which is concordant with the European guidelines [ 6 ]. Even though 60 days is considered a cut-off value for a successful surgery, the best results are thought to be obtained in patients aged between 45 and 60 days [ 3 ]. Some studies suggested surgery may be performed even before the age of 30 days, achieving jaundice clearance in all patients [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was a reason to change the focus toward a faster diagnostic, given that younger patients age have a less advanced stage of the disease, with consecutively, better results. The ideal time for surgery is currently considered between the first 30–45 days of life, although when performed at 45–60 days it seemed to be associated with better results [ 3 , 4 ]. An important tool for the early detection of BA would be a screening program in which the efficiency of stool color cards is highlighted [ 5 ] together with case centralization in high volume centers [ 6 ].…”
Section: Introductionmentioning
confidence: 99%